Relationships among livestock, structure, and regeneration in Chilean Austral Macrozone temperate forests - Huertas Herrera, Alejandro; Toro Manríquez, Mónica del Rosario; Salinas Sanhueza, Jaime; Rivas Guíñez, Fernanda; Lencinas, María Vanessa; Martínez Pastur, Guillermo José (Trees, Forests and People)
A Macrozone is a socioecological region with shared geographic and demographic characteristics. Within the Chilean Austral Macrozone (43° to 56° SL), the native temperate forests serve as a crucial resource, offering multiple ecosystem services to local communities. These forests significantly support animal husbandry practices involving cattle, horses and sheep. However, introducing these exotic species affects natural regeneration and compromises their long-term sustainability. This study proposes a new classification of the temperate forests in the Chilean Austral Macrozone based on structure parameters and determine their relationships with animal husbandry and natural regeneration. Data were obtained from Chile´s National Forest Inventory (NFI) (2001–2010), including 195 inventory plots (500 m2) with 21 tree species. We redefined the forest categories described in NFI according to the proportional basal area of each tree species at each plot. We used two levels of analysis: forest composition (Level 1), which includes general categories such as mono-specific (dominated by a single tree species), bi-specific (dominated by two tree species), and multi-specific forests (dominated by multiple tree species), and forest type (Level 2), which includes specific species (e.g., Nothofagus pumilio) or species groups (e.g., N. pumilio - N. dombeyi) with economic relevance. We evaluated the data using univariate and multivariate analyses. We found 18 forest types in the Austral Macrozone, in contrast to the three traditionally recognized forest types used in the NFI (e.g., lenga, evergreen, coihue de Magallanes). Livestock was observed in all forest types, where Nothofagus forests showed that regeneration in N. antarctica and N. pumilio were higher with livestock than without livestock breeding (Hedges´ g > 0.51). The natural regeneration of the studied forests was influenced by animal husbandry, environmental variables (bioclimatic and topographic factors), and forest structure. Our data suggested the importance of ...